Beyond vision:Cataract and health status in old age, a narrative review - Mencucci, Rita; Stefanini, Simone; Favuzza, Eleonora; Cennamo, Michela; De Vitto, Chiara; Mossello, Enrico (Frontiers in Medicine, 2023)
Cataract is a leading cause of visual impairment in old age. Lens opacification is notoriously associated with several geriatric conditions, including frailty, fall risk, depression and cognitive impairment. The association is largely attributable to visual impairment, while other mechanisms, associated with extraocular comorbidity and lifestyle, might partly explain this correlation. Available literature suggests that cataract surgery may be effective in decreasing fall risk, improving depressive symptoms and limiting the risk of cognitive impairment and dementia incidence, although intervention studies on these outcomes are still limited. In this review we also emphasize the need to move from the concept of visual acuity to functional vision, especially in the context of the geriatric patient. Research is needed regarding the effect on the cited outcomes of different cataract treatment strategies, such as systematic bilateral versus monolateral surgery and use of different intraocular lenses.